Supply Chain Management for Digital Enterprise, Psychological Aspect of Adaptation - Vladimir F. Ukolov; Valentin Y. Afanasyev (International Journal of Supply Chain Management, 2020)
Abstract- Information inaccuracy can adversely affect supply chain performances by lack of inventories, delay in delivery times, lost sales and decreased customer satisfaction. The article deals with the little-studied scientific problem of the psychological aspect of digital enterprise management in the fuel and energy complex and its high-tech enterprises. The purpose of this study, described in the article, is to develop the approaches to the use of digital enterprise personnel psychological management, which allows it to become value-oriented, adaptive to virtual technologies, psychologically resistant to changes and effective in supply chain management. The study used the methods of situational, structural and dynamic analysis, which provided the opportunity to study the psychology of digital enterprise management, to trace its changes in time, space and in close relationship with other phenomena. They used the systematic approach during the evaluation of digital enterprise management psychology. The study allowed to obtain scientific and practical results and conclusions. It noted that despite the revolutionary development of information technologies at digital enterprises and the increasing use of the virtual environment during the work with information, a person remains the main subject of activity. His subconscious is the deep layers of human existence, more and more involved in the processes of digitalization. However, this should not happen spontaneously. The subconscious mind can be edited by the employee himself and, with the help of special methods and techniques, be maintained at enterprises via psychological management in such a way that the digitalization processes do not conflict with the main value orientations of an individual, society and a state. The use of value-oriented psychology of management at digital enterprises of the fuel and energy sector will increase their stability, will enrich the culture of digital production and will improve the key performance of supply chain indicators significantly through the use of a psychological factor.